SAFFRON (CROCUS SATIVUS) AND THE NEMATODE FAUNA OF ITS RHIZOSPHERE (Multidisciplinary Journal of Science and Technology, 2025)
This article provides in-depth and comprehensive information on the nematode fauna of field saffron (Crocus sativus L.) and its rhizosphere. A scientific analysis is provided based on new, previously unrecognized and understudied data on the biology of the saffron plant, the characteristics of the rhizosphere environment, the types of phytonematodes found in it, their population composition, the influence of ecological and agrotechnical factors, as well as the interaction of nematodes with each other and with other microorganisms in the rhizosphere of saffron. The article covers the identification of nematodes, population dynamics and their impact on saffron yield, as well as integrated management measures, based on modern morphological and molecular methods.